2007
DOI: 10.14411/fp.2007.041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii in small mammals from the Ardennes Region, France

Abstract: Abstract. Serum samples from 218 small mammals trapped in forest and grassland in the Ardennes region (North-eastern France) were tested for antibodies to Toxoplasma gondii. Using the modified agglutination test, positive results were found in 4/92 Apodemus sp., 3/64 Clethrionomys glareolus, 0/26 Microtus agrestis, 0/4 Micromys minutus, 3/5 Sorex sp., 2/9 Arvicola terrestris, and 7/18 Talpa europaea. Toxoplasma gondii was not isolated from the heart of seropositive individuals after bioassay in mice. Seropreva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 11 publications
2
27
1
3
Order By: Relevance
“…However, infection rates in our study (0–2.3%, depending on the testing method) were significantly lower than the prevalence in the French study, where 39% of the moles from North-Eastern France tested positive [20]. …”
Section: Resultscontrasting
confidence: 71%
“…However, infection rates in our study (0–2.3%, depending on the testing method) were significantly lower than the prevalence in the French study, where 39% of the moles from North-Eastern France tested positive [20]. …”
Section: Resultscontrasting
confidence: 71%
“…In the wild environment, small mammals are considered staples in the diet of several species of wild felines and, possibly, the domestic cat (CAÑÓN-FRANCO et al, 2013). Some studies have shown that the rate of T. gondii infection in these felines is related to the predator-prey relationship, and therefore dependent on the availability of food for species considered to be prey (AFONSO et al, 2007). In the Parque da Cidade, there are no top-level predators, such as wild cats, so the population of domestic cats grows without interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that in populated areas, especially those involved in agricultural practice, mice constitute by a large margin the most abundant intermediate host, but there is explicit evidence for extensive T. gondii infection in many other small wild mammals that are prey for domestic cats (Afonso et al 2007). In favour of the view that the mouse is subject to significant selective impact from T. gondii, it should also be noted that the mouse also suffers from two weaknesses following infection that appear to be associated with the adaptive strategy of T. gondii, namely the selective modification of its olfactory abreaction to cat urine in favour of a positive tendency to favour this smell (Vyas et al 2007), thus increasing the accessibility of infected mice to capture by cats; and the ability to transmit T. gondii vertically without significant injury to the progeny (Owen & Trees 1998), enabling persistence of the parasite in a mouse lineage or deme despite the short average lifetime of individual mice.…”
Section: Coadaptation Of Host and Parasitementioning
confidence: 99%